2012
DOI: 10.1055/s-0031-1290074
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular Conjugate Addition of α,β-Unsaturated Lactones Having an Alkanenitrile Side Chain: Stereocontrolled Construction of Carbocycles with Quaternary Carbon Atoms

Abstract: An efficient method for constructing carbocycles with all-carbon quaternary stereocenters has been developed on the basis of a stereoselective cyclization reaction of α,β-unsaturated lactones having an alkanenitrile side chain. Treatment of the substrate with lithium hexamethyldisilazide (LiHMDS) in the presence of triisopropylsilyl chloride (TIPSCl) led to the generation of the corresponding α-cyano carbanion species which readily underwent an intramolecular conjugate addition reaction. It was found that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…We found that this addition occurred upon the treatment of am ixture of 13 and TIPSCl [15] with NaHMDS in Et 2 Oa t À78 8 8C, which produced O-silyl N,O-ketene acetal 27 in situ. We found that this addition occurred upon the treatment of am ixture of 13 and TIPSCl [15] with NaHMDS in Et 2 Oa t À78 8 8C, which produced O-silyl N,O-ketene acetal 27 in situ.…”
Section: Angewandte Chemiementioning
confidence: 90%
See 1 more Smart Citation
“…We found that this addition occurred upon the treatment of am ixture of 13 and TIPSCl [15] with NaHMDS in Et 2 Oa t À78 8 8C, which produced O-silyl N,O-ketene acetal 27 in situ. We found that this addition occurred upon the treatment of am ixture of 13 and TIPSCl [15] with NaHMDS in Et 2 Oa t À78 8 8C, which produced O-silyl N,O-ketene acetal 27 in situ.…”
Section: Angewandte Chemiementioning
confidence: 90%
“…[11] As one of the key steps,w ed esigned an intramolecular conjugate addition (Michael addition) of a,bunsaturated N-methoxy-N-methylamides (commonly named Weinreb amides [12] )b earing an alkanenitrile side chain (Scheme 1b; 5!7). [15] In addition, if such additions were to occur with facial discrimination, the sterically much less demanding cyano group would induce stereoselective cyclization,r esulting in simultaneous construction of contiguous quaternarytertiary stereocenters.M oreover,t he potential different reactivities between the sterically congested cyano group and Weinreb amide groups in the product 7 would facilitate the further transformations. [15] In addition, if such additions were to occur with facial discrimination, the sterically much less demanding cyano group would induce stereoselective cyclization,r esulting in simultaneous construction of contiguous quaternarytertiary stereocenters.M oreover,t he potential different reactivities between the sterically congested cyano group and Weinreb amide groups in the product 7 would facilitate the further transformations.…”
mentioning
confidence: 99%
“…In this regard, we have previously reported an alternative approach for the prevention of analogous retro additions, via trapping of the intermediate as the corresponding ketene silyl acetal in an intramolecular Michael addition of α, β unsaturated lactones. 10 Additionally, if such additions proceeded with facial discrimination, the signi cantly less sterically demanding cyano group 11 would induce the stereoselective cyclization, which would result in the simultaneous construction of contiguous quaternary tertiary asymmetric stereocenters. Furthermore, the potentially different reactivities between the sterically congested cyano group at the ring juncture and the Weinreb amide group in the cyclization product 7, would facilitate further transformations.…”
Section: Challenges and Strategiesmentioning
confidence: 99%
“…We therefore carefully examined and optimized the reaction conditions, focusing on the solvent and additives for the cyclization of Weinreb amides 30 and 31 (Scheme 5). When the standard O methyl Weinreb amide 30 was treated with NaHMDS in the presence of a bulky silylating agent, triisopropylsilyl chloride (TIPSCl) 10 and hexamethylphosphoric triamide (HMPA) in THF at 78 , the intramolecular Michael addition proceeded smoothly to afford cyclic O silyl N,O ketene acetal 32 in situ. Treatment of the reaction mixture with tetrabutylammonium uoride (TBAF) in a one pot manner gave a diastereomeric mixture of the desired cyclization product 33 and its C8,C9 diastereomer 34 20 in a 45:55 ratio ( 99% yield).…”
Section: Construction Of the Ab Ringmentioning
confidence: 99%
“…7 The cyclization reaction is thought to proceed through formation of the N-silyl ketene imine intermediate under the influence of TMSOTf and Et 3 N. Indeed, a 85:15 diastereomeric mixture of acyclic nitrile 3 was found to undergo isomerization to afford a 60:40 mixture of the diastereomers under similar conditions. 8 These results suggested that the combined use of TMSOTf and Et 3 N shows promise for generating an N-silyl ketene imine from the corresponding nitrile without requiring a strong base such as lithium diisopropylamide (LDA).…”
Section: Scheme 1 Typical Examples Of Nucleophilic Addition To Nitronesmentioning
confidence: 99%